3Rs e i prodotti del futuro: Act Now for the Sustainable Development Goals - SDGs in STEM Education - Zambrotta, Maria (Chimica nella Scuola, 2024)
The work 3Rs and the product of the future, developed by the three authors Iro koliakou, Anders Floren and Maria Zambrotta, aims to stimulate reflection on more sustainable productions, starting with both raw and recycled materials. The abbreviation “3 R’s” stands for Reduce, Reuse, and Recycle and encapsulates the aims of the activities: the impact of daily plastic use is highlighted, several workshop activities on the study and reuse of wool, and the production of cement from mussel shells are presented. The goals are to engage students in active learning and stimulate their critical thinking. In the online publication curated by Science on Stage, the following three sections are developed: (1) Bioplastics concerning an in-depth look at the use of plastics and the production of bioplastics; (2) Wool as a resource; in this regard some teaching units are published on wool as a raw material for bio-based products and the production of different products through simple chemistry experiments are reported; (3) How to make cement from mussel shells in which the production of cement using biomaterials is illustrated. In this article will be presented only the section related to the Wool.